(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Swami Vivekanand was a great sanyasi and bona fide nationalist. He believes that spirituality and religion both are the main theme of India. Spiritual nationalism of Vivekanand is a unique synthesis of India’s cultural heritage, its civilisation and religious philosophy, and modern aspirations. Vivekananda’s nationalism is based not only on political or territorial ground of nationalism but also on spiritual ethos of India for national identity. He opined that real nationalism must be rooted in spirituality, as it is the soul of Indian civilisation. Vivekananda stressed on regeneration of India through the revival of Indian culture, spiritual values, and moral strength. His vision of nationalism was inclusive, transcending caste, creed, and regional divisions, and focused on service to humanity as the highest form of patriotism. He linked the religion with nation-building to create a strong, self-reliant India that could contribute to global economy. His philosophy continues to inspire discourses on national identity, cultural resilience, and the role of spirituality in public life. He emphasised that the strength of India comes from religious and spiritual ideas. He understands that religion is backbone of India’s national life. He opined that national life of Indian citizens should be organised on the basis of religious principles. Vivekananda brought back eternal things of Indian Scriptures like Vedas and Upanishads to build up country’s development and faith in individuals. Vivekananda invoked the masses, worked for physical and moral strength of people and created consciousness among Indians for their country’s pride towards ancient glory and greatness. Thus, he became the eminent architect of modern nationalism in Bharat (India). Vivekananda gave importance to the concept of strength and fearlessness. Vivekananda announced that ‘the essence of my religion is strength’. A nation is made only by its individuals and that is why Vivekananda requested all individuals to inculcate the qualities of prowess, human dignity and respect for all. He had deep love and compassion in his heart for poor. He used to say that for the betterment of the poor, it is important to give them education and message of spirituality. He was of the opinion that let the poor be fed and they would take care of the rest. He opined that awakening of masses is important. Vivekananda opined that India may emerge as a determined and stable nation only on the basis of religion. Thus, the paper will enquire Vivekananda’s spiritual nationalism and give some insights how his ideas is relevant at present scenario.